Demonstration Method: An Effective Alternative in Improving Student Mathematics Learning Outcomes in Elementary School - Wiwin Mariyanto; Yonarlianto Tembang; Martha Betaubun; Any Niatun (Edumaspul: Jurnal Pendidikan, 2023)
The demonstration method is a very effective method, because it helps students to find answers with their own efforts based on facts or correct data by demonstrating both directly and through the use of teaching media that are in accordance with the material presented. Talking about the effectiveness of the demonstration method, the importance of this method can be seen from the way it is applied in learning, one of which is in mathematics learning. Learning mathematics is one of the learning that is often a scary thing for every student. Therefore, to overcome this, a method that suits students during learning is needed. Take this into account. So, the purpose of this study is to see the effectiveness of the demonstration method on student learning outcomes in mathematics subjects. This research is a classroom action study, where this research was carried out on grade II students at SD Negeri 2 Merauke for the 2022/2023 school year. In this study, 24 students were the subjects of the study. By applying two cycles with two meetings each in each cycle, the study also used tests and observations as research data. As a result, there was a very significant improvement in student learning outcomes starting from cycle I to cycle II. Therefore, it is expected that the role of teachers is to advance in the achievements achieved by students, so teachers must be more creative and innovative to create learning that is fun, easy to understand and able to increase student interest so that learning objectives can be achieved.